Evaluation of the milk physicochemical and microbiological patterns in different lactation phases in year seasons in milk farms of Paraná State - Brazil - Fagan, Eder Paulo; Tamanini, Ronaldo; Fagnani, Rafael; Beloti, Vanerli; Barros, Márcia de Aguiar F.; Jobim, Clóves Cabreira (Semina: Ciências Agrárias, 2008)
The objective of this study was to evaluate the physicochemical and microbiological parameters of milk in different lactation phases during a year in two Dairy farms producing type A milk (Brazilian Standards) and classified as Farm 1 (G1) and Farm 2 (G2). The 320 raw milk samples were collected to analyze acidity Dornic, California Mastit Test (CMT), Somatic Cells Counting (SCC) and Cryoscopy (0H) during four seasons, in the period of January 00 to January 005. To data statistical analyses a General linear model (GLM) was used. The CMT, the SCC, acidity Dornic and Cryoscopy (0H) results were not significant (P>0.05), during the year seasons, between the farms and in the different lactation phases. The SCC (9 5.000 cells/mL) average results are in disagreement with the legislation. To the Dornic acidity and Cryoscopy (0H), the values had not exceeded the limit demanded by IN5 . The results of mesophilic aerobic organisms counting during autumn (G ) and during spring (G ) had revealed a disagreement with IN5 . High levels of coliforms (TC) and Escherichia coli (EC) were observed in G in all seasons when compared with G . It was demonstrated that the physical-chemistry and microbiological quality are important to handling practical during milks.